Testing and calibration of an ultraviolet-a radiation sensor based on GaN photodiode - Theyirakumar .J,; Gopir .G,; Yatim .B,; Sanusi .H,; Megat Mahmud .P.S,; Hoe .P.C, (Universiti Kebangsaan Malaysia, 2011)
An ultraviolet A (UVA) radiation intensity sensor with responsivity in the wavelength range of 320-360 nm was developed based on a gallium nitride (GaN) photodiode. In this sensor system, a GaN photodiode in reverse-biased mode converts the radiation intensity into current, which was then converted and amplified into an output voltage by a transimpedance amplifier (TIA), or current-voltage converter, consisting of an operational amplifier and a feedback resistor. For a narrowband UV source, the radiation intensity could be calculated from the values of the output voltage, feedback resistor, photodiode responsivity and photodiode effective area. The sensor was tested by performing measurements over different values of UV source wavelength, source distance, ambient temperature and sampling time. For calibration with a broadband UV source, the GaN-UVA sensor was used simultaneously with a standard Si-UVA sensor to measure solar radiation. The observed linear relationship between the sensors’ outputs enables us to convert the output voltage of the GaN-UVA sensor to UVA intensity. Thus, we have successfully developed, tested and calibrated an ultraviolet A radiation sensor based on the GaN photodiode.